2022
DOI: 10.21203/rs.3.rs-1301637/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Novel Obesity- and Lipid-Related Indices as Predictors of Abnormal Glucose Tolerance in Chinese Women with Polycystic Ovary Syndrome

Abstract: Purpose We aimed to evaluate the performance of Chinese visceral adiposity index (CVAI), visceral adiposity index (VAI), lipid accumulation product (LAP), triglyceride glucose (TyG) as indices in screening abnormal glucose tolerance (AGT) in Chinese women with polycystic ovary syndrome (PCOS), using the oral glucose tolerance test (OGTT) as a reference test. In addition, we essentially compared the abilities of these indices with body mass index (BMI), waist circumference (WC), fasting plasma glucose (FPG). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, we also managed to distinguish the subgroup defined as pre-MetS. Thus far, the literature concerning the pre-MetS subgroup has been rather scarce, and the previous studies have focused on specific subgroups, such as PCOS, and have mainly been conducted in Asia or South America [ 22 , 23 , 24 , 25 ]. The inherent difficulty has been related to the heterogeneous nature of the group, as it has been characterized with a significantly higher HOMA-IR and TG in comparison to MHO, and with significantly lower WC and LDL and GGTP when compared to MetS.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, we also managed to distinguish the subgroup defined as pre-MetS. Thus far, the literature concerning the pre-MetS subgroup has been rather scarce, and the previous studies have focused on specific subgroups, such as PCOS, and have mainly been conducted in Asia or South America [ 22 , 23 , 24 , 25 ]. The inherent difficulty has been related to the heterogeneous nature of the group, as it has been characterized with a significantly higher HOMA-IR and TG in comparison to MHO, and with significantly lower WC and LDL and GGTP when compared to MetS.…”
Section: Discussionmentioning
confidence: 98%
“…These measurements can accurately and comprehensively quantify the mass and distribution of fat and muscle. In a series of studies, percent body fat and fat mass index were found to be more valuable in predicting metabolic abnormalities than traditional measurements such as BMI and WC 12,13 . In addition, images measured with water‐fat magnetic resonance imaging, dual‐energy X‐ray absorptiometry, and ultrasound can also reflect whole‐body composition in a detailed and intuitive fashion; however, these approaches are not suitable for routine detection because of their high cost, complexity, and radioactivity 14 …”
Section: Introductionmentioning
confidence: 99%